Variability of cardiovascular magnetic resonance (CMR) T1 mapping parameters in healthy volunteers during long-term follow-up - Siepen, Fabian aus dem; Baumgärtner, Christian; Müller-Hennessen, Matthias; André, Florian; Messroghli, Daniel; Ochs, Marco; Riffel, Johannes; Giannitsis, Evangelos; Katus, Hugo; Friedrich, Matthias; Buß, Sebastian Johannes (Open Heart, 2018)
Background Myocardial T1 and extracellular volume (ECV) derived from cardiovascular MRIs are more and more widely accepted as important markers for diagnosis, risk prediction and monitoring of cardiac disease. Yet data regarding long-term stability of myocardial T1 mapping are lacking. The aim of this study was to investigate the long-term stability of native and postcontrast T1 mapping values in healthy volunteers. - Methods 18 strictly selected healthy volunteers (52±10 years, 12 men) were studied on a Philips Achieva 1.5 Tesla scanner. T1 relaxation times were measured before and 15 min after a bolus contrast injection of gadolinium diethylenetriamine penta-acetic acid (DTPA) (0.2 mmol/kg) using a single-breath-hold modified Look-Locker inversion recovery 3(3)3(3)5 sequence. ECV was calculated using native and postcontrast T1 times of myocardium and blood correcting for blood haematocrit. Exams were repeated 3.6±0.5 years later under the same conditions and using the same scan protocols. - Results Cardiac biomarkers (high-sensitivity troponin T and N terminal pro-brain natriuretic peptide) remained unchanged, as well as left ventricular mass, and global and longitudinal function. No significant change occurred regarding native T1 times (1017±24 ms vs 1015±21 ms; P=0.6), postcontrast T1 times (426±38 ms vs 413±20 ms; P=0.13) or ECV (22%±2% vs 23%±2%; P=0.3). Native T1 time and ECV appeared to be better reproducible than postcontrast T1, resulting in lower coefficients of variation (ECV: 3.5%, native T1: 1.3%, postcontrast T1: 6.4%) and smaller limits of agreement (ECV: 2%/−2%, native T1: 39 ms/−35 ms, postcontrast T1: 85 ms/−59 ms). - Conclusions During long-term follow-up, native T1 and ECV values are very robust markers, whereas postcontrast T1 results appear less stable.